ANALISIS DESAIN FORMULIR RINGKASAN RIWAYAT MASUK DAN KELUAR PASIEN DEWASA RAWAT INAP DI RUMAH SAKIT TK. IV KENCANA SERANG - Sattari Khoirunnisa (Poltekkes 'Aisyiyah Banten, 2022)
Background: A summary form of admission and discharge history is a medical record form that is used to record a summary of the course of the disease from the time the patient enters until the patient leaves the hospital. Therefore, it is one of the forms that are immortalized, so it is necessary to design a design that is in accordance with the standards. Research Objectives: To identify the physical aspects, anatomical aspects, and aspects of the contents of the summary form of admission and discharge history of adult patients at the Kindergarten Hospital. IV Kencana Serang in 2022. Research Methodology: This study used descriptive research with observation and interview methods. The subjects in this study were medical record officers and the object in this study was a summary form of admission and discharge history of adult patients. The research instrument used observation sheets and interview guidelines. Research results: From the physical aspect, the material is HVS 75 gram paper, rectangular shape, HVS F4 paper size, the color of the paper is white with black ink writing. From the anatomical aspect, the heading in the form of the title of the form has been included, the subtitles are missing, the name of the hospital has been included, the hospital logo is not included, the revision number is not included. page numbers are included. Introduction in the form of the title of the form. Instruction in the form of * Adult and child patients. Body in the form of top margin (5 cm), bottom margin (2 cm), side margin (1.5 cm), back margin (1.5 cm). Spacing 1.15 spaces. Vertical and horizontal rules. Type Style Times New Roman with font size 11. The way of recording is done by handwriting. Close in the form of a clear name and signature has been included. From the aspect of content, the completeness of the data items is appropriate. Terminology / Terms in the form of diagnosis, complications, anesthesia, transfusion. Abbreviations in the form of Date, Goal, NRP, NIP, Kls, dr, Sp, Lk / Pr, Is / Kk / Kp / H / B, S / N / J / D. The symbol is the symbol * Adult and child patients. Suggestion: It is necessary to redesign the entry and exit history summary form for adult patients from the physical, anatomical and content aspects.